2006
DOI: 10.1002/chem.200501594
|View full text |Cite
|
Sign up to set email alerts
|

High‐Spin‐ and Low‐Spin‐State Structures of [Fe(chloroethyltetrazole)6](ClO4)2 from Synchrotron Powder Diffraction Data

Abstract: The spin-crossover complex [Fe(teec)(6)](ClO(4))(2) (teec = chloroethyltetrazole) exhibits a 50 % incomplete spin crossover in the temperature range 300-30 K. Time-resolved synchrotron powder diffraction experiments have been carried out to elucidate its structural behavior. We report crystal structure models of this material at 300 K (high spin) and 90 K (low spin), as solved from synchrotron powder diffraction data by using Genetic Algorithm and Parallel Tempering techniques and refined with Rietveld refinem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
9
0

Year Published

2007
2007
2017
2017

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(9 citation statements)
references
References 38 publications
0
9
0
Order By: Relevance
“…This choice was justified by the observation that the spin transition is present in iron(II) complexes of 1-substituted tetrazoles with perchlorate or tetrafluoroborate as counteranions. [25,35,36] Spin crossover is exhibited by monomeric complexes based on alkyl, [35,37] cycloalkyl [38] and fluorinated alkyl tetrazoles [36,39] as well as polymeric systems containing bis- [22][23][24] and tris-tetrazoles [26] as bridging ligands. In the present study, the magnetic behaviour of 1·BF 4 differs completely from that observed for the perchlorate analogue.…”
Section: Introductionmentioning
confidence: 99%
“…This choice was justified by the observation that the spin transition is present in iron(II) complexes of 1-substituted tetrazoles with perchlorate or tetrafluoroborate as counteranions. [25,35,36] Spin crossover is exhibited by monomeric complexes based on alkyl, [35,37] cycloalkyl [38] and fluorinated alkyl tetrazoles [36,39] as well as polymeric systems containing bis- [22][23][24] and tris-tetrazoles [26] as bridging ligands. In the present study, the magnetic behaviour of 1·BF 4 differs completely from that observed for the perchlorate analogue.…”
Section: Introductionmentioning
confidence: 99%
“…Very recently, N-substituted tetrazolate ligands have received increasing attention because of the lowtemperature ferromagnetism and thermal spin-state transition of their metal complexes. 4 A series of Cu II or Fe II complexes of 1-substituted tetrazoles (1-R-tetrazoles), R ) alkyl, 5 phenyl, 6 chloroethyl, 7 and methoxyethyl 4a were found to be a new type of low-temperature ferromagnetism or thermal spin-state transition. Unfortunately, all of these complexes have low-dimensional structures because the unfunctionalized N-monosubstituents show no coordination ability and thus disfavor the formation of higher-dimensional structures.…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, a series of tetrazolate-based complexes (5-R-tetrazoles, R = alkyl, pyridyl, phenyl, chloroethyl, and methoxyethyl) with transition metals (i.e. Zn, Cd, Cu and Ag) were found to possess intriguing architectures as well as potential applications as functional materials [2][3][4][5][6]. For example, Xiong et al have successfully synthesized two novel acentric metal-organic coordination polymers, [Zn(OH)(3-ptz)] and [CdN 3 (3-ptz)] (3-ptz = 5-(3-pyridyl)tetrazolate), which display second harmonic generation (SHG) responses in the solid state [3a].…”
mentioning
confidence: 99%